Analysis of Peer Feedback Effects on Students’ Achievement in Writing Fantasy Stories - Noftriana Ciptaningdiah, Eka; Aisyah, Siti; Taufik, Kani Sulam (ETERNAL (English Teaching Journal), 2026)
This study aims to examine the effectiveness of peer feedback in improving Grade 11 students’ achievement in writing fantasy stories.. The research used purposive sampling with 36 participants. Employing a mixed-methods approach, the study combines quantitative analysis of pre-test and post-test writing scores with qualitative insights from questionnaires and interviews to examine both the measurable impact and students’ perceptions of peer feedback in writing fantasy stories. Quantitative results revealed a statistically significant improvement in students’ writing performance, with the mean score increasing from M = 87.86 (SD = 2.58) on the pre-test to M = 92.56 (SD = 2.27) on the post-test, representing an approximate 14,67% gain (p < .01). Qualitative findings reveal that students perceive peer feedback as beneficial for enhancing creativity, structure, and idea development in their fantasy stories, as well as for fostering critical thinking and collaboration. The findings suggest that integrating peer feedback into writing instruction can enhance both students’ linguistic skills and creative engagement.